Snack bar formulation with beetroot (Beta vulgaris. L) flour as iron sources for adolescent girls - Zakia Umami; Lusi Anindia Rahmawati; Amalina Ratih Puspa (Alma Ata University Press, 2021)
ABSTRAK Latar Belakang: Prevalensi anemia di Indonesia pada remaja putri meningkat dari 37.1% menurut Riskesdas 2013 menjadi 48.9% pada tahun 2018. Snackbar merupakan cemilan yang digemari oleh remaja. Penambahan tepung umbi bit pada snackbar sebagai sumber zat besi diharapkan menjadi alternatif cemilan sehat bagi remaja putri.Tujuan: Untuk mengembangkan formula snack bar.Metode: Penelitian ini menggunakan desain eksperimental. Formulasi terdiri atas dua tahap yaitu tahap pertama menentukan formula terbaik tanpa penambahan tepung umbi bit. Tahap kedua yaitu formulasi dengan penambahan tepung umbi bit dengan tiga taraf yang berbeda yang terdiri atas F1 40 gram, F2 50 gram, F3 60 gram. Analisis kandungan zat gizi dilakukan melalui uji proksimat dan spektrofotometri.Hasil: Formula terbaik adalah F1 dengan penambahan tepung umbi bit sebanyak 40 gram. F1 mengandung 11,99% protein; 10,62% lemak; 53,04% karbohidrat; 4,76 mg zat besi (32% memenuhi AKG remaja putri dan 21,6% ALG kelompok umum), dengan total energi sebesar 355,75 kkal/100g.Kesimpulan: Tepung umbi bit dapat digunakan untuk meningkatkan kandungan zat gizi snack bar, dimana dapat membantu memenuhi kebutuhan zat gizi remaja putri khususnya kebutuhan zat besi. Untuk penelitian selanjutnya, dapat ditambahkan pangan sumber protein hewani agar dapat meningkatkan penyerapan zat besi.KATA KUNCI: remaja; snackbar; tepung; umbi bit; zat besi ABSTRACTBackground: In Indonesia, the prevalence of anemia in adolescent girls increased from 37.1% (Riskesdas 2013) to 48.9% (Riskesdas 2018). A snack bar is one of the snacks favored by adolescents. The addition of beetroot flour as a source of iron to snack bars is expected to be an alternative healthy snack for adolescent girls. Objectives: The objective of this study was to develop a snack bar formulationMethods: This study used an experimental design. The snack bar was made in two stages. The first stage was to determine the best formula without adding beetroot flour, and the second stage was adding beetroot flour in the following amounts: 40 g (F1), 50 g (F2), and 60 g (F3). Analysis of nutrient content was carried out through the proximate test and spectrophotometry.Results: The best formula was (F1), i.e., administering 40 g of beetroot flour. F1 contained 11.99% of protein, 10.62% of fat, 53.04% of carbohydrates, and 4.76 mg of iron (32% fulfilling Fe needed by adolescent girls based on the Dietary Reference Intake and 21.6% of the Reference Intake for the general category), with a total energy of 355.75 kcal/100 g.Conclusions: Beetroot flour could be used to improve nutrient profiles of snack bars, which could be used to fulfill the nutrient needs of adolescents, especially for iron. For the next research, a new formulation is needed by adding animal protein sources to increase iron absorption.KEYWORDS: adolescent; beetroot; flour; iron; snack bar